Impacts of biodiversity-positive intercropping systems on food quality, safety and the consumer acceptance: A case study of intercropped wheat - Cheng Liu; Rosa Safitri; Sander van Leeuwen; Bengu Ozturk; Domantas Girzadas; Eva-Tsvetalina Christoff; Caspar Krampe (Journal of Agriculture and Food Research)
Climate change and biodiversity loss are challenging the food-production system and urging a transition towards a sustainable food system. Various strategies are being proposed, including the adoption of biodiversity-positive cropping systems such as intercropping. Most existing studies explore the benefits of intercropping for yield and the environment, while ignoring further implications at the post-harvest stage. The current study aims to evaluate the impacts of intercropping on food safety, food quality and the associated consumer acceptance through a theoretical transition from wheat monoculture to intercropping wheat with a selection of companion crops. In the absence of quantitative monitoring data, qualitative assessments via literature review and expert interviews identified key safety hazards (e.g., mycotoxins, plant toxins, heavy metals, pesticide residues) and quality parameters (e.g., protein and gluten content for baking). Consumer preferences, analysed through a conjoint analysis, showed a preference for naturally produced products, with low pesticide use, but also display different consumer preferences as resembled by four consumer segments. A knowledge-based dashboard was developed to integrate all the findings into a decision-support system. For policymakers, producers and supply-chain actors, the study underscores the need to align agronomic practices with safety standards, invest in consumer education, and foster collaborations to ensure sustainable, high-quality food production. Successfully navigating this transition requires balancing climate and biodiversity goals with the delivery of safe, nutritious, and consumer-preferred products.